TINJAUAN YURIDIS TERHADAP PENETAPAN HARGA LIMIT LELANG EKSEKUSI BARANG JAMINAN PADA PERUM PEGADAIAN (Studi Kasus Perum Pegadaian Cabang Kuningan Jawa Barat) - , ikke purnamasari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is intended to find out the implementation of determining the limit price of the collateral goods auction in the Kuningan pawnshop and to find out whether the debtor as the owner of the goods has the law protection of the auction limit price determination by the pawnshop. This study used judicial empirical research that is an approach that study the secondary data first and continued by conducting the primary data study which is directly obtained from the field by using questionnaire and interview. The data analysis used in this research is quantitative analysis with deductive conclusions drawing. The research results show that the implementation of determining the limit price in the Kuningan pawnshop is done by 2 methods that are determining the Auction Market Value or re-apprisal (NPL) an Minimum Auction Value (NML). In determining the NPL, the Kuningan pawnshop uses the auction center market price (HPPL) as the basis. The HPPL is determinate based on the golg and precious metals basis price which is issued by the Head Office while in determining the NML is by calculating the borrowed money, equity rented and the auction charge. In fact, the implementation of NPL yeet still not appropriate with the form letter num.44/UI.1.00211/2006 concerning colleteral goods auction which require the HPL determination being suited with the auction center markel price. And the market value in the aucttion area. The law protection concerning the debtor as the owner of the auction goods on however the limit price determination is still not fully protected, it can be seen from the method in determining the limit price which has obeyed the HPDL, though the HDL has been known yet the Kuningan Pawnshop tent to comply the stipulations given by HPPL, as a result the is a price differentiation where the price limit is lower than the market price whereas in the Form Letter Num.44/UI.1.00211/2006 has to be based on the HPDL and HPPL depend on which price is higher.